Mechanical Properties of Polypropylene Warp-Knitted Hernia Repair Mesh with Different Pull Densities - Xu, Wanli (Polymers (Basel), 2018)
The medical polypropylene monofilament with a diameter of 0.10 mm was used as the material. Four different pull densities and two different warp run-ins were set up on the electronic traverse high-speed Tricot warp knitting machine, with the gauge of E28. The raw material was used to knit four variations of single bar plain knitted fabrics with 1 in-1 miss setting. Each variation required eight samples. The mechanical properties of the above 32 warp-knitted fabric samples are tested, including their tensile stress (in both vertical and horizontal directions), tearing stress (in both vertical and horizontal directions) and bursting stress. The results obtained shows that the relationship between the vertical, the horizontal stress, and the pull density are not monotonic. The tensile stress in the vertical direction firstly decreases and then increases with an increase of the pull density; however, the tensile stress in the horizontal direction firstly increases and then slightly decreases with an increase of the pull density; again the vertical tensile stress of all fabrics was always higher than the horizontal tensile stress. The bursting stress has a positive linear relation to the pull density. The vertical tearing stresses of four samples were greater than the horizontal tearing stress.